The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.5713/ajas.16.0424
|View full text |Cite
|
Sign up to set email alerts
|

Carcass characteristics and meat quality of lambs that are fed diets with palm kernel cake

Abstract: ObjectiveThe aim was to evaluate carcass characteristics, cut yield, and meat quality in lambs that were fed different inclusion levels of palm kernel cake.MethodsForty-five woolless castrated male Santa Inês crossbred sheep with an initial average body weight of 23.16±0.35 kg were used. The experimental design was a completely randomized design with five treatments, with palm kernel cake in the proportions of 0.0%, 7.5%, 15.0%, 22.5%, and 30.0% with nine replications per treatment. After slaughter, the gastro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
(22 reference statements)
0
6
0
Order By: Relevance
“…However, there was no difference for cut yield as a function of the levels of inclusion of PKC in our study except neck weight. The results found by dos Santos et al (2017) showed there was a reduction in the commercial cut weight, except for the neck weight for animals that were fed on 7% of PKC which provided the greatest neck weight and the lowest weight was observed those fed with 30% of PKC. The utilization of five concentrations of crude glycerin (0, 3, 6, 9 and 12% of DM) as a substitute of ground corn by Lage et al (2014) justified the well-balanced distribution of muscle and fat in the body of animals since commercial cuts represent the tissue distribution in different regions of the carcass.…”
Section: Carcass Characteristicsmentioning
confidence: 90%
See 1 more Smart Citation
“…However, there was no difference for cut yield as a function of the levels of inclusion of PKC in our study except neck weight. The results found by dos Santos et al (2017) showed there was a reduction in the commercial cut weight, except for the neck weight for animals that were fed on 7% of PKC which provided the greatest neck weight and the lowest weight was observed those fed with 30% of PKC. The utilization of five concentrations of crude glycerin (0, 3, 6, 9 and 12% of DM) as a substitute of ground corn by Lage et al (2014) justified the well-balanced distribution of muscle and fat in the body of animals since commercial cuts represent the tissue distribution in different regions of the carcass.…”
Section: Carcass Characteristicsmentioning
confidence: 90%
“…Kirton et al (1972) reported that the live weight and nutritional status of animals could affect the production efficiency of carcass offal. This is while noting that the inclusion of PKC in the diet caused a certain degree of feed restriction thereby lowering the weight of the primary metabolic organs such as the liver, heart, and small and large intestines (dos Santos et al, 2017).…”
Section: Carcass Characteristicsmentioning
confidence: 99%
“…According to Santos et al (2017), NDF from tropical feedstuffs is characterized by highly heterogeneous degradation, which is responsible for significant changes in the rumen-reticulum; it first influences potentially digestible NDF, which provides energy to animals by breaking down fiber carbohydrates, and secondly affects the indigestible portion of NDF that is unable to be utilized by rumen microorganisms.…”
Section: Resultsmentioning
confidence: 99%
“…Effects of Acacia Albida leaf supplementation on weight and length of digestive tract components in young sheep (6 months). Probability those obtained by dosSantos et al (2017) on carcass characteristics and meat quality of lambs fed palm kernel meal-based diets (0.43; 0.43; 0.42; 0.36 and 0.34kg respectively). The difference thus observed could be explained by the fact that animals can gain weight even during periods of feed restriction; this can occur in situations where body weight gain does not represent the genetic potential of the animals, as evidenced by the study by…”
mentioning
confidence: 76%
“…However, animals fed a ration supplemented with 400g of Acacia Albida leaves had significantly (p<0.05) higher spleen weights than those of the other two groups, which remained comparable. Santos et al (2017) where high-energy feeds such as corn and soybean meal were replaced by palm kernel meal, altering nutrient availability while reducing animal body weight gain. This while considering that the inclusion of palm kernel meal in the diet resulted in some degree of feed restriction.…”
Section: Effects Of Acacia Albida Leaf Supplementation On the Weight ...mentioning
confidence: 99%